Stabilization of crude oil emulsions using different surfactants - Akbari, Sweeta; Nour, Abdurahman Hamid (International Journal of Innovative Research and Scientific Studies, 2018)
Emulsions can be found in different industries such as petroleum, food, cosmetic and pharmaceutics. Generally, there are two types of emulsions in petroleum industries: water-in-oil (W/O) and oil-in-water (O/W). The aim of this research was to evaluate the stability of W/O emulsions using different emulsifiers such as Span 80, Span 83, Triton-x-100, DEA, and LSWR with different concentrations (1.5 and 2.5) vol%. All the emulsions were prepared at (20-80) vol% and 2000 rpm. The result of this study showed that the most stable emulsions were prepared by Span 80. However, LSWR formed the most unstable emulsions. In addition, it was also found that the concentration of emulsifier can significantly affect the emulsion stability.